THE INFLUENCE OF GREEN ACCOUNTING AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE: STUDY ON BUMN BANK IN INDONESIA - Dharmawati, Tuti; Mayndarto, Eko Cahyo; Djaini, Aditya; Utama, Andrew Shandy; Ardianingsih, Arum (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research highlights the importance of Green Accounting (GA) and Corporate Social Responsibility (CSR) in increasing company value, especially in state-owned banks in Indonesia. The results of the regression analysis show that both GA and CSR have a significant positive influence on company value. Together, they provide a stronger impact, confirming that continuous integration practices can create competitive advantages and strengthen a company's image. These findings have immediate power for business practitioners and decision makers, providing a foundation for more sustainable and socially responsible strategies. Although this research makes a valuable contribution, it is worth noting limitations such as geographic focus and specific industries, which may provide directions for future research.